Mandala: an agent-based platform to support interoperability in systems-of-systems - Mendes, Altair; Loss, Stefano; Cavalcante, Everton; Lopes, Frederico; Batista, Thais (2018 IEEE ACM 6th International Workshop on Software Engineering for Systems of Systems (SESoS), 2018)
A particular challenge to the construction of systems-of-systems (SoS) is the high heterogeneity of their constituent systems, thereby making interoperability an important issue to be tackled. This paper introduces Mandala, a platform to support interoperability in SoS. Mandala aims to offer a software layer to integrate heterogeneous, independent information systems without significantly changing their implementation or even knowing details about each system. The proposal relies on (i) business process models to represent activities associated to SoS global missions and (ii) software agents to support asynchronous communication among autonomous components. This paper presents an evaluation of Mandala and its interoperability mechanisms through a case study using information systems within a smart city scenario.